1997
DOI: 10.1021/ic970833z
|View full text |Cite
|
Sign up to set email alerts
|

New Small-Ring Cyclogermanes:  Syntheses and X-ray Crystal Structures

Abstract: Reaction of GeCl 2 ‚dioxane with 2 equiv of Li(THF) 2.5 Ge(SiMe 3 ) 3 in hexane afforded moderate yields of two cyclopolygermanes. A cyclotrigermane, (Ge(SiMe 3 ) 2 ) 3 , was characterized by NMR spectra, elemental analyses, and an X-ray crystal structure determination. It crystallized from pentane in the R3 hc space group (rhombohedral) with a ) 19.294(3) Å, R ) 31.89(1)°, V ) 1781 Å 3 , and Z ) 2. The Ge 3 core consisted of an equilateral triangle with a Ge-Ge distance of 2.460(1) Å, the shortest so far meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 18 publications
(47 reference statements)
3
47
0
Order By: Relevance
“…The first step of this reaction sequence is likely analogous to what happened in the reactions described by Stalke, 9 Klinkhammer, 10 and Mallela. 11 However, the acyclic examples can react by another 1,2-trimethylsilyl shift to give an isomeric silylene, which eventually inserts into the Si–Si bond, thus forming a three-membered ring. While the cyclic silagermene 4 and digermene 4a could also undergo an additional 1,2-trimethylsilyl shift, final insertion of the thus formed silylene or germylene into a Si–Si or Si–Ge bond is not likely, due to the cyclic nature of the molecule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first step of this reaction sequence is likely analogous to what happened in the reactions described by Stalke, 9 Klinkhammer, 10 and Mallela. 11 However, the acyclic examples can react by another 1,2-trimethylsilyl shift to give an isomeric silylene, which eventually inserts into the Si–Si bond, thus forming a three-membered ring. While the cyclic silagermene 4 and digermene 4a could also undergo an additional 1,2-trimethylsilyl shift, final insertion of the thus formed silylene or germylene into a Si–Si or Si–Ge bond is not likely, due to the cyclic nature of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…Using (Me 3 Si) 3 GeLi as the nucleophile, Mallela et al reported similar chemistry leading to hexakis(trimethylsilyl)germirane. 11 …”
Section: Introductionmentioning
confidence: 99%
“…A yellow-orange derivative [128] contains a [Ge(SiBu)]3 + cation and a tfpb anion. The three Si atoms are nearly coplanar with the central triangle, and the overall structure is essentially the same as for two other derivatives [129,130], In the dark red derivative [129] the Ge-Ge bond distances in the Ge3 triangle are 223.9(4) and 252.2(4) pm (x2) (average 242.8(4) pm). The Ge-Ge bond distances of the three membered ring are almost equal, ranging from 232.9(2) to 234.3(2) pm (average 233.5(2) pm).…”
Section: Trimeric Compoundsmentioning
confidence: 70%
“…The structure of tris(trimethylsilyl)silylcyclotetragermane 7 (M=Si [22]) closely resembles that of its tris(trimethylsilyl)germyl counterpart 7 (M=Ge, [15]). Both compounds have all frans-geometry.…”
mentioning
confidence: 87%
“…The cyclotrigermane 2 [15] crystallizes as a very hygroscopic, transparent, hexagonal slabs. Three germanium atoms form a regular triangle with a short Ge-Ge distance of 2.460 A.…”
mentioning
confidence: 99%